Do Inflows or Outflows Dominate? : Global Implications of Capital Account Liberalization in China - Bayoumi, Tamim (IMF Working Papers; Working Paper ;, 2013)
This paper assesses the implications of Chinese capital account liberalization for capital flows. Stylized facts from capital account liberalization in advanced and large emerging market economies illustrate that capital account liberalization has historically generated large gross capital in- and outflows, but the direction of net flows has depended on many factors. An econometric portfolio allocation model finds that capital controls significantly dampen cross-border portfolio asset holdings. The model also suggests that capital account liberalization in China may trigger net portfolio outflows as large domestic savings seek to diversify abroad.